Media Representation: Coverage of the Nepali Army's Rescue and Relief Operations - Aryal, Kundan (Unity Journal, 2023)
This paper explores the media representation of the Nepali Army in its efforts of rescue and relief operations at home and abroad. In recent decades, the Nepali Army personnel have been directly involved in multiple public–welfare affairs along with their primary responsibilities of national security and territorial protection. Media representation of the Nepal Army has been examined from the perspective of Stuart Hall's classification of representation of meaning through language works. To unfold the media representation of the Nepali Army in its significant roles and core principles, I have taken a sample of the Nepali mass media content from the coverage of the Sankatmochan rescue and relief operations launched by the Nepal Army in two major national dailies, Kantipur and Nagarik in the aftermath of the 2015 Gorkha earthquake, for a period of a fortnight. The Nepali Army’s effective manoeuvre of the earthquake relief embodies the institution’s relevance in serving the cause of humanity along its core tasks of maintaining security, peace and order at home and abroad. In this paper, the coverage of different activities run by the Nepal Army is characterized as either reflective, intentional or constructionist. Moreover, the content concerning such rescue and relief operations has been contributing to shaping the image of the institution.